Rheology and Structure of Lithium‐Ion Battery Electrode Slurries. Issue 10 (6th September 2022) - Reynolds, Carl D.; Hare, Sam D.; Slater, Peter R.; Simmons, Mark J. H.; Kendrick, Emma
Abstract : The rheology of electrode slurries dictates the final coating microstructure. High slurry viscosity creates excess pressure and limits coating speed, elasticity causes instabilities leading to coating defects and high flow causes slumping leading to thin, poorly structured coatings. However, due to differing solvent systems and components, and the complex nature of the many competing interactions, finding the source of these detrimental rheological properties can be difficult. Herein, a systematic rheological characterization of all components of an industrially relevant anode and cathode slurry is presented. Through a combinatory approach, the additive nature of the interactions is explored, using steady shear, small and large amplitude oscillatory shear to give insight into the underlying structure, which is vital to develop novel, more sustainable formulations. For water‐based anodes, the polymeric binder dictates the rheology, thickening the slurry, allowing efficient suspension of the active material particles, which only contribute an increase in viscosity. For N‐methyl pyrrolidine (NMP)‐based cathodes, the conductive additive forms a weakly gelled network in NMP which flows under coating shear. The binder, as well as thickening, also functions to adsorb to active material surfaces, displacing additive and leaving it free to form this network, which is key to the electronic properties of the dried electrode. Abstract : The rheology of industrially relevant lithium‐ion battery slurries and their components are systematically characterized. These properties are key to understanding the flow during manufacture (e.g., mixing and coating). Rheology also gives key insights into the underlying structure, necessary to propose new, more sustainable formulations and strategies to optimize new material slurries to drop into the current manufacturing process.